PENGADILAN HIBRIDA SEBAGAI UPAYA PEACEBUILDING PASCA RUNTUHNYA KEKUASAN KHMER MERAH DI KAMBOJA - Muhammad Rusli Arafat (UIR Press, 2023)
The enforcement of international criminal law is an effort to fulfill the international community's sense of justice for serious international crimes. Cambodia came into the international spotlight under Pol Pot. At that time Pol Pot proclaimed Cambodia as a new country under the name Democratic Kampuchea. He referred to 1975 as